Analisis Kejahatan Korupsi Ditinjau Dari Kejahatan Terorganisir - Ciek Julyati Hisyam; Elin Nur Fadila; Ersa Novia; Farhan Pria Syawaldi; Naia Regitha; Rini Febriyani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corruption crimes are crimes committed jointly between several people or groups of people committed in a government or private institution. The purpose of the research is to explain the crime of corruption in terms of organized crime. The research method uses a descriptive qualitative approach conducted in women's prisons using informants and key informants located in women's prisons. Data collection techniques were carried out by in-depth interviews with informants and key informants. The results of the study state that the corruption crime committed by the informant is an act of organized crime because a person agrees to the request of his superior who wants to work together in a company to engage in illegal activities at the national level with the aim of making a profit.